Recent Developments in U.S. Cyberlaw - Stewart, David P. (2018)
This article surveys recent developments in domestic U.S. law relating to key issues in Internet (or Cyber) Law. Rapid technological advances have posed serious challenges to traditional legal doctrines and approaches relating to (for example) fundamental issues of privacy, freedom of speech and expression, and protection against unwarranted governmental intrusion. How has the law responded to these key challenges? Since the United States lacks a comprehensive legislative structure addressing these issues, most of the recent developments have come in the form of judicial decisions.